PENGARUH TERPAAN TAYANGAN YOUTUBE DEHAKIMS TERHADAP SIKAP ORANGTUA MENGENAI ANAK MENONTON SATWA - Randy Prayoga Priansyah; Imani Satriani; Muslim Muslim (UNIVERSITAS PAKUAN, 2022)
This study discusses the effect of exposure to Dehakims Youtube shows on parents' attitudes about children watching animals at Pamoyanan, South Bogor. The purpose of this study was to determine how much influence exposure to Dehkims Youtube shows had on parents' attitudes about their children watching animals. The theory used in this research is cultivation theory. This study uses quantitative methods, the data obtained by the sample survey method. The author makes a questionnaire that is in accordance with the indicators of the variables to be studied and asks respondents to fill out the questionnaire. Furthermore, the authors perform data calculations using the SPSS version 25 application. The conclusion of this research, which is based on the results of the determination test, shows that Dehakims Youtube shows have an influence on parents' attitudes about children watching animals in Pamoyanan, South Bogor, by 53.4%.. This means that Dehakims Youtube shows only have an influence of 53.4% on parents' attitudes about children watching animals at Pamoyanan, South Bogor, while the remaining 46.6% is caused by other factors not examined in this research.